2020
DOI: 10.14814/phy2.14466
|View full text |Cite
|
Sign up to set email alerts
|

Acute performance and physiological responses to repeated‐sprint exercise in a combined hot and hypoxic environment

Abstract: Team and racket sport athletes repeatedly produce brief bouts of maximal power output (~10 s) interspersed with insufficient recovery period (~60 s) during competition. This physical fitness component is known as "repeated-sprint ability" (RSA) (Bishop, Girard, & Mendez-Villanueva, 2011; Girard, Mendez-Villanueva, & Bishop, 2011). Recent studies have shown that several weeks of repeated-sprint training in hypoxia further improves RSA compared with the same

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
(66 reference statements)
1
13
0
1
Order By: Relevance
“…Greater peak and mean power outputs with heat exposure (HOT and HH) would be associated with elevated muscle temperature. In support, Yamaguchi et al ( 2020) [31] demonstrated that hot environment (35 °C, 50 % rH) significantly elevated muscle temperature during RSE (using similar exercise protocol with the present study) compared with thermoneutral environment (20 °C, 50 % rH). An acute heat exposure with an elevated muscle temperature increases repeated-sprint performance [32], probably due to muscle-related factors, such as faster contraction velocity and increased anaerobic ATP turnover in fast-twitch fibers [33].…”
Section: Discussionsupporting
confidence: 89%
“…Greater peak and mean power outputs with heat exposure (HOT and HH) would be associated with elevated muscle temperature. In support, Yamaguchi et al ( 2020) [31] demonstrated that hot environment (35 °C, 50 % rH) significantly elevated muscle temperature during RSE (using similar exercise protocol with the present study) compared with thermoneutral environment (20 °C, 50 % rH). An acute heat exposure with an elevated muscle temperature increases repeated-sprint performance [32], probably due to muscle-related factors, such as faster contraction velocity and increased anaerobic ATP turnover in fast-twitch fibers [33].…”
Section: Discussionsupporting
confidence: 89%
“…Combining hypoxia and hot condition decreased moderate-intensity cycling time to exhaustion (Girard and Racinais, 2014) and 90-min simulated soccer performance (Aldous et al, 2015) compared with hypoxia or hot alone, probably due to higher blood lactate concentration and greater reduction of plasma volume related to the combination of impaired O 2 availability and increased cardiovascular strain (Aldous et al, 2015;Girard and Racinais, 2014). In contrast to prolonged exercise, repeated short maximal sprint performance was not negatively affected by combined hot and hypoxia (Dennis et al, 2021;Yamaguchi et al, 2020). Therefore, the performance outcome in the present study was supported by the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The trials were conducted in normoxic (NOR; 23℃, relative humidity [RH] = 50%, FiO 2 = 20.9% [sea level]), normobaric hypoxic (HYP; 23℃, RH = 50%, FiO 2 = 14.5% [simulated altitude of 3,000 m]) and hot normobaric hypoxic (HH; 35℃, RH = 50%, FiO 2 = 14.5%) conditions in a single-blind, cross-over study. Moderate hypoxia (FiO 2 = 14.5%) and heat stress (35℃) were selected based on previous studies combining the hypoxic and hot environments during exercise (Girard and Racinais, 2014;Yamaguchi et al, 2020). The order of the trials was randomized and counterbalanced.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…E essa resistência à fadiga, durante os sprints repetidos, depende diretamente do modo de exercício, por exemplo ciclismo vs corrida, sendo que a potência decrescente, durante protocolos de sprints repetidos de ciclismo (10-25%), foram relatadas como maiores, do que aquelas dos protocolos de corrida (5 a 15%) (FITZSIMONS et al, 1993). Ademais, o desenvolvimento da fadiga durante os sprints repetidos também parece depender de outros três fatores: da carga resistiva (mecanicamente, vento ou resistência eletromagnética) (FALGAIRETTE et al, 2004;MATSUURA et al, 2011) da superfície (tipo de solo, aclive e declive); e fatores de estresse ambiental (calor e hipóxia) (YAMAGUCHI et al, 2020). Assim como, obviamente, a resistência à fadiga depende de condições clínicas alteradas, como regulação da rigidez, hipoglicemia e lesão muscular, que a compromete durante protocolos de sprints repetidos (BISHOP; GIRARD; MENDEZ-VILLANUEVA, 2011; GIRARD; MENDEZ-VILLANUEVA; BISHOP, 2011).…”
Section: 2sprints Repetidos E Fadigaunclassified